2021
DOI: 10.1021/acs.orglett.1c02023
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Photorhabdus temperata ssp. Cinereal 3240 Zwitterionic Trisaccharide Repeating Unit

Abstract: Zwitterionic carbohydrate modifications, such as phosphoethanolamine (PEtN), govern host−pathogen interactions. Whereas it is recognized that these modifications stimulate the host immune system, the purpose of PEtN modification remains largely descriptive. As an enabling step toward studying this carbohydrate modification, we report a synthesis of the P. temperata zwitterionic trisaccharide repeating unit. The 32-step synthesis was enabled by H-phosphonate chemistry to install the PEtN arm on a poorly reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Similar outcomes were observed with the hydride sources NaBH 4 and LiEt 3 BH. During our studies, a report by Townsend and co-workers identified NaBH 3 CN to be effective at reducing primary alkyl iodides . Applying analogous conditions (NaBH 3 CN, DMF, 100 °C) to our case also proved beneficial, delivering the taxol core ( 14 )confirmed by X-ray crystallographic analysisin 72% yield.…”
Section: Results and Discussionmentioning
confidence: 57%
“…Similar outcomes were observed with the hydride sources NaBH 4 and LiEt 3 BH. During our studies, a report by Townsend and co-workers identified NaBH 3 CN to be effective at reducing primary alkyl iodides . Applying analogous conditions (NaBH 3 CN, DMF, 100 °C) to our case also proved beneficial, delivering the taxol core ( 14 )confirmed by X-ray crystallographic analysisin 72% yield.…”
Section: Results and Discussionmentioning
confidence: 57%
“…H-phosphonates are a class of phosphonylated intermediates that have been used in the syntheses of other glycerophospholipids, including phosphatidyl inositols [ 34 , 35 , 36 , 37 ], phosphatidyl ethanolamine [ 38 ], phosphatidyl choline [ 38 ], and phosphatidyl serine [ 20 , 38 ]. They have also been used in the total synthesis of glycophospholipids [ 39 , 40 , 41 ], as well as in nucleoside-based phospholipids [ 24 ] and drugs [ 42 ]. To our surprise, they have not, however, been utilized in the synthesis of PG.…”
Section: Resultsmentioning
confidence: 99%
“…disclosed that CA produced by the gut commensal bacteria could significantly increase the longevity of the host Caenorhabditis elegans , and this effect was conserved across different species . Attracted by the significant biological activities and the unique structures of capsular polysaccharides, a panel of glycans relevant to their repeating units have been synthesized; notwithstanding, O -Ac-decorated oligosaccharides are rarely involved. Here we report the first chemical synthesis of a proposed CA hexasaccharide repeating unit ( 1 ).…”
mentioning
confidence: 99%